Global Living Ethics: Unveiling Practical and Theoretical Synergies Through Reflexive Balancing - Boudreau LeBlanc, Antoine (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2024)
Exploring the complex landscape of bioethics, this article combines the theoretical insights of the Potterian Global Bio-Ethics approach with bioethics research methods, aiming for actionable ethical compromises in governance. The Potterian approach transcends traditional disciplinary boundaries, adopting John Dewey’s pragmatist view, and bringing into convergence philosophical and empirical methods. I advocate for a synergy between micro-scale local-empirical and macro-scale global-rational approaches. Presenting a hands-on case for bioethicists, I emphasize a ‘Global’ bioethics perspective, grounded at the individual scale. Drawing on concepts like ‘boundary-object’ and ‘hybrid community’ from Susan Star and Michel Callon, I propose a reflexive methodology with tools for mapping, framing, and shaping ethical inquiries, to avoid fallacies and embed values in problem-solving. This approach strives to connect meta-ethical reflections with daily bioethical challenges, promoting a coherent, reflexive, and pragmatic methodology.